2015
DOI: 10.1007/s12272-015-0557-z
|View full text |Cite
|
Sign up to set email alerts
|

Anti-inflammatory activity of sappanchalcone isolated from Caesalpinia sappan L. in a collagen-induced arthritis mouse model

Abstract: Sappanchalcone, a bioactive flavonoid isolated from the heartwood of Caesalpinia sappan L. possesses anti-inflammatory effects. We studied the efficacy of sappanchalcone in attenuating collagen-induced arthritis (CIA) in a mouse model of rheumatoid arthritis. Sappanchalcone was purified to homogeneity from the chloroform fraction of the methanolic extract of C. sappan, and identified using mass spectrometry and (1)H-nuclear magnetic resonance spectroscopy. CIA-induced male DBA/1J mice were divided into control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 35 publications
2
24
0
1
Order By: Relevance
“…15 Compound 2 isolated as a yellow powder. The 1 H NMR spectrum of 2 showed an ABX spin coupled system at δ Although no biological activity tests were conducted on the isolated compounds, literature search revealed that sappanchalcone (1) exhibited anti-inflammatory, [18][19][20] neuroprotective, 21,22 inhibition of antigen-induced beta hexosaminidase release, 23 anti-influenza viral, 24 growth inhibition and induction of apoptosis in human oral cancer cells. 25 Caesalpiniaphenol G (2) showed growth inhibition and induction of apoptosis in human premyelocytic cancer cells.…”
Section: Resultsmentioning
confidence: 99%
“…15 Compound 2 isolated as a yellow powder. The 1 H NMR spectrum of 2 showed an ABX spin coupled system at δ Although no biological activity tests were conducted on the isolated compounds, literature search revealed that sappanchalcone (1) exhibited anti-inflammatory, [18][19][20] neuroprotective, 21,22 inhibition of antigen-induced beta hexosaminidase release, 23 anti-influenza viral, 24 growth inhibition and induction of apoptosis in human oral cancer cells. 25 Caesalpiniaphenol G (2) showed growth inhibition and induction of apoptosis in human premyelocytic cancer cells.…”
Section: Resultsmentioning
confidence: 99%
“…CIA was induced in 6- to 8-week-old male DBA/1J mice as previously described 29 30 . Briefly, the mice were immunized intradermally at the tail base with bovine CII (100 μl of 1 mg/ml) emulsified in complete Freund’s adjuvant containing killed Mycobacterium tuberculosis (Difco, USA) (day 0).…”
Section: Methodsmentioning
confidence: 99%
“…Caesalpinia sappan L., a type of traditional Chinese herb, possesses extensive pharmacological activities, including antioxidant, 1,2 anti-inflammation 3,4 and antimicrobial, 5 Sappanone A (SA), a homoisoflavanone isolated from the dry heartwood of Caesalpinia sappan L., has been reported to have antioxidant and anti-inflammatory activities as well. 6 Moreover, SA has demonstrated a good effect on the treatment of allergic asthma, 7 osteoclastogenesis 8 and melanogenesis 9, and displays a good application prospect in clinical practice.…”
Section: Introductionmentioning
confidence: 99%